2019
DOI: 10.1111/ijfs.14205
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of phytochemical profiles, cellular antioxidant and anti‐proliferative activities in five varieties of wampee (Clausena lansium) fruits

Abstract: Summary Wampee (Clausena lansium) fruit is a seasonal food containing high levels of bioactive phytochemicals which may be useful for health benefits. This study compared the phytochemical composition, total and cellular antioxidant activities (CAA) as well as anti‐proliferative activities of five different varieties of wampee fruits. The results showed that six phytochemical compounds (vanillic acid, ferulic acid, rutin, syringin, catechin and hesperetin) were found in wampee fruits. Total antioxidant activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…TPC was a positive correlation obtained with FRAP at the 1% level. Similar trends were reported by [61], who noticed that phenolic content had significant positive correlations with FRAP (r � 0.992, p < 0.01) in wampee fruits.…”
Section: Correlations Among Phytochemical Compoundssupporting
confidence: 88%
See 1 more Smart Citation
“…TPC was a positive correlation obtained with FRAP at the 1% level. Similar trends were reported by [61], who noticed that phenolic content had significant positive correlations with FRAP (r � 0.992, p < 0.01) in wampee fruits.…”
Section: Correlations Among Phytochemical Compoundssupporting
confidence: 88%
“…Pearson's correlation coefficient was performed in order to illuminate the relationship of all of the measured parameters. Different literature reported the Pearson correlations among the secondary metabolites and antioxidant activity in several plant species [60,61]. Analytical results indicated that the best correlation was between TFC and FRAP (0.731 * * ) as well as between TPC and FRAP (0.590 * * ), followed by TFC and ABTS (0.573 * * ) ( Table 3).…”
Section: Correlations Among Phytochemical Compoundsmentioning
confidence: 92%
“…Nitrogen radical scavenging activities (DPPH and ABTS) were determined. DPPH radical scavenging activity was evaluated as described by Ye et al 26 . Each extract (0.1 mL) was mixed with 2.0 mL of a DPPH solution (0.2 mM) and left for 30 min.…”
Section: Number Of Extractionsmentioning
confidence: 99%
“…ROS scavenging activities (ORAC, hydroxyl radical, superoxide anion radical, hydrogen peroxide) were determined. ORAC was measured as the methods described by Ye et al 26 and Kim and Lim 25 . Each extract (0.025 mL) was mixed with 0.15 mL of fluorescein sodium salt solution (78 nM), left for 15 min at 37 °C, and added with 0.025 mL of AAPH (250 mM).…”
Section: Number Of Extractionsmentioning
confidence: 99%
See 1 more Smart Citation